IMPROVE CRITICAL THINKING STUDENTS IN INDONESIA FOR NEW LEARNING MANAGEMENT SYSTEM - Iqbal Desam Girinzio; Ahmad Ramadan; Dimas Bagus Saputra; Gadis Mustika; Sulistio (Pandawan Sejahtera Indonesia, 2023)
In Indonesian 4.0's goal for a knowledge-based economy, critical thinking skills have been given more weight. Given the seriousness of the problem, the researchers gathered a focus group of nine professionals in August 2017 and asked them to help create a new critical thinking education methodology. From this, the authors developed the